TP53 and KRAS co-mutations are associated with worse outcomes in mucinous ovarian carcinomas - Yingao Zhang; Savannah Barkdull; Panayiotis D. Kontoyiannis; Alejandra Flores Legarreta; David M. Gershenson; Preetha Ramalingam; Michael M. Frumovitz; Anil K. Sood (Frontiers in Oncology)
ObjectiveMucinous ovarian carcinomas (mOC) often harbor unique molecular alterations differentiating them from other epithelial ovarian carcinoma subtypes. We sought to characterize the somatic genomic mutation patterns in mOC and elucidate their associations with oncologic outcomes.MethodsAll patients with mOC treated at a single institution between 2005–2023 were identified, and those with validated tumor molecular profiling (TMP) using next-generation sequencing of somatic variants were included. Progression-free survival (PFS) and overall survival (OS) were calculated on a Kaplan-Meier estimator. Multivariable analysis was performed using Cox regression models.ResultsForty patients were included in this retrospective cohort; 34 (85%) had at least 1 genomic alteration on TMP, with a median of 3 mutations (range 0-30). TP53 (68%) and KRAS (63%) were most frequently altered, and 21 patients (53%) had tumors with TP53/KRAS co-mutations. Patients with TP53/KRAS co-mutations were younger (median 27.9 vs 54.1 y, p=0.01) and were more likely to have early-stage disease (86% vs 47%, p=0.02) than patients without these co-mutations. On multivariable analysis, TP53/KRAS co-mutations were associated with decreased PFS (adjusted hazard ratio [aHR] 4.02, 95% confidence interval [CI] 1.46-12.5, p=0.01) and OS (aHR 21.4, 95% CI 4.28-156, p<0.001). On subgroup analysis of stage I tumors (N=27), the presence of TP53/KRAS co-mutations remained independently associated with worse OS (aHR 8.66, 95% CI 1.50-93.8, p=0.03).ConclusionA substantial proportion of mOCs have concurrent TP53 and KRAS alterations on TMP, and this may portend worse survival, even for patients with early-stage disease. TMP could be a useful tool for prognostication and can be considered for patients with mOC at the time of diagnosis.